Research on attribute-based encryption with keyword search for cloud storage - Zhi-qiang ZHU; Hang SU; Lei SUN; Zuo-hui LI (网络与信息安全学报)
To safeguard the sensitive data stored on the cloud and promote the efficiency of data sharing simulta-neously,a secure flexible and efficient attribute-based encryption scheme with keyword search is proposed,which designs an index generation mechanism that requires the private key of data owner to resist the keyword guessing attack,supports one-to-many application scenarios based on the linear secret shared access structure,introduces the conjunctive subset keyword search technique and online/offline technique to improve search flexibility and efficien-cy.Theoretical analysis and experimental evaluation show that the proposed scheme enjoys high efficiency.